Real-time reaction monitoring by probe electrospray ionization mass spectrometry - Yu, Zhan (2010)
Probe electrospray ionization (PESI) is a modified version of the electrospray ionization (ESI), where the capillary for sampling and spraying is replaced by a solid needle. High tolerance to salts and direct ambient sampling are major advantages of PESI compared with conventional ESI. In this study, PESI-MS was used to monitor some biological and chemical reactions in real-time, such as acid-induced protein denaturation, hydrogen/deuterium exchange (HDX) of peptides, and Schiff base formation. By using PESI-MS, time-resolved mass spectra and ion chromatograms can be obtained reproducibly. Real-time PESI-MS monitoring can give direct and detailed information on each chemical species taking part in reactions, and this is valuable for a better understanding of the whole reaction process and for the optimization of reaction parameters. PESI-MS can be considered as a potential tool for real-time reaction monitoring due to its simplicity in instrumental setup, direct sampling with minimum sample preparation and low sample consumption.